Arginase and ceruloplasmin activity in the serum of patients with polysomnography-detected sleep bruxism - Martynowicz, Helena; Michałek, Monika; Waliszewska-Prosół, Marta; Macek, Piotr; Kusnerż, Agnieszka; Lachowicz, Gabriella; Przegrałek, Jakub; Galińska, Zuzanna; Poręba, Rafał; Madziarska, Katarzyna; Gać, Paweł (Frontiers in Neurology, 2025)
BackgroundArginase and ceruloplasmin are enzymes of redox balance involved in the metabolism of nitric oxide. Arginase competes with nitric oxide synthase (NOS) for L-arginine and hence plays a crucial role in the arginase/NOS balance of maintaining proteins and the appropriate nitric oxide (NO•) level in the serum. On the other hand, ceruloplasmin (CP) is an acute- phase protein responsible for the metabolic balance of copper and iron. For this study it was to investigate the serum concentrations of enzymes involved in the redox balance, namely arginase type I (Arg1) and CP, in a group of patients with and without sleep bruxism (SB), which was diagnosed by polysomnographic examination.Methods75 adults (35 women and 40 men, mean age 49.12) underwent a full- night of video polysomnography according to standards set out by the American Academy of Sleep Medicine. The concentration of Arg1 and CP in the serum, was determined using ELISA Kits.ResultsThe results showed that the concentration of Arg1 and CP was significantly lower in individuals with SB, irrespective of bruxism severity. Regression analysis revealed that only in the group of patients with higher Arg1 and CP concentrations, was there a negative linear relationship with the bruxism episode index (BEI).ConclusionThe results suggest that there is an oxidative imbalance in patients with SB, independent of the severity of bruxism. Higher plasma levels of Arg1 and CP were related to a lower BEI, potentially as the result of a protective biochemical balance against oxidative stress and inflammation in the SB.